2021
DOI: 10.1039/d0cp05341d
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic structural features of water in aqueous–reline mixtures of varying compositions

Abstract: Water–urea hydrogen bonds partially restore the tetrahedral coordination of water molecules in aqueous reline solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 107 publications
3
18
0
Order By: Relevance
“…The quantitative difference between water content that corresponds to a transition to a dilute aqueous solution obtained by Kumari et al [ 286 ] and Sapir et al [ 292 ] could be explained by the differences in the water models used in these works. Sarkar et al [ 300 , 301 ] confirmed the results obtained by Kumari et al [ 286 ] and Sapir et al [ 292 ] and investigated changes in water structure with the increase in the fraction of reline [ 300 ] and pure ChCl [ 301 ]. They showed that in the presence of reline, water–water contacts are replaced with contacts between water and urea molecules and chloride anions, which affects water structure significantly.…”
Section: Main Directions Of Investigationssupporting
confidence: 56%
“…The quantitative difference between water content that corresponds to a transition to a dilute aqueous solution obtained by Kumari et al [ 286 ] and Sapir et al [ 292 ] could be explained by the differences in the water models used in these works. Sarkar et al [ 300 , 301 ] confirmed the results obtained by Kumari et al [ 286 ] and Sapir et al [ 292 ] and investigated changes in water structure with the increase in the fraction of reline [ 300 ] and pure ChCl [ 301 ]. They showed that in the presence of reline, water–water contacts are replaced with contacts between water and urea molecules and chloride anions, which affects water structure significantly.…”
Section: Main Directions Of Investigationssupporting
confidence: 56%
“…For both systems, a blue-shift of the ν­(CH) signal is observed upon water addition which might generally be ascribed to the progressive hydration of the alkyl moiety of the choline cation. , Different from the bands of urea discussed above, Figure evidences an almost linear behavior, suggesting that water insertion around choline is somewhat more gradual and that the hydration of its hydrophobic portion is not fully attained in the explored concentration range. At any rate, the data support the occurrence of a progressive substitution of cation–anion interactions with cation–water ones at high hydration degrees, , which is probably driven by the formation of new anion–water interactions (as will be discussed below). Note that in this case also, the position of the ν­(CH) band is different in the two DESs with low water contents, which reflects the change in the interactions felt by the cation upon anion substitution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Fuelled by searching for environmentally friendly solvents for sustainable chemical processes, deep eutectic solvents (DESs) have emerged as green designer solvents with a wide range of applications. A typical DES consists of an HB acceptor (HBA) and an HB donor (HBD), mixed in the eutectic molar ratio. , DES nanostructures, stabilized by intercomponent HB interactions, can be further tuned by the addition of cosolvents capable of disrupting the native HB networks. As water can act as both HBA and HBD, these neoteric solvents are highly water-miscible and hygroscopic. , Recent reports demonstrate that water addition in the eutectic mixtures influences the DES nanostructures and consequently impacts their physicochemical properties . Trends in these properties suggest an upper limit of DES hydration, above which DES behaves like an aqueous solution. …”
mentioning
confidence: 99%
“…Although various reports studied the disruption of reline nanostructure at certain hydration levels, ,,, all the studies focused on understanding the phenomenon from the solvent’s perspective in the absence of any dissolved solute. The effect of increasing water content in reline from the solute’s perspective has yet to be explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation